Role of agricultural technology on socio-economic development in Hathras district, UttarPradesh - Ahmad, Mumtaj; Islam, Pasarul; Siddiqui, Shamsul Haque (National Geographical Journal of India, 2022)
Agriculture in India has experienced a signicant transformation in the past fty years, with agriculture being more and more oriented to a productivist form of socio-economic production. Introduction of new agricultural technologies, high yielding varieties of seeds, improve access to irrigation, education, efcient use of fertilizers and extension services are capable of enhanced productivity per unit of land. Increased production further reects on socio-economic transformation in rural communities. The study uses secondary data from various sources published by the Government of India and the Government of Uttar Pradesh. The study covers the period between 2000-01 and 2014-15 to analyze the role of agricultural technologies on socio-economic transformation in Hathras district. The methodology adopted for the present study are Data Interpolation or Extrapolation, Yang's Crop Yield Index, Dayal's Labour Productivity, Data Standardisation technique Z- score, and Composite Z score. The study concludes that the district has experienced tremendous technological changes in agricultural practices, agriculture induced better productivity and productivity further leads to overall socio-economic transformation